SURVEI KESADARAN MENTAL MAHASISWA UPN VETERAN YOGYAKARTA DI ERA DIGITAL DAN COVID-19 - Adara Bintang Nugroho; Hanafiah Beno Al Asri; Ardhia Ajeng Pramesti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
In Indonesia, the Basic Health Research Data (Riskesdas) 2018 shows the prevalence of emotional mental disorders as indicated by symptoms of depression and anxiety for ages 15 years and over reaches around 6.1% of the total population of Indonesia or the equivalent of 11 million people. This number has the potential to continue to increase, because people's lives have changed due to the Covid-19 pandemic. Mental health is an issue that cannot be ignored. Changes in people's behavior that have become the new normal such as work from home, study from home and even a number of religious activities have also switched to using live streaming. Thus, the house becomes the center of activity of a family which has the potential to cause mental health disorders. This study aims to find out how students who are running online lectures are aware of mental health problems. The research method was conducted by survey method with random sampling technique. The results of the research show that there is a tendency for respondents to self-diagnose due to incomplete understanding of mental health issues. Therefore, it is hoped that the service strategy for improving the quality of mental health at UPN